The Hyperbilirubinemia and Potential Predictors Influence on Long-Term Outcomes in Sepsis: A Population-Based Propensity Score-Matched Study - Peng, Milin; Deng, Fuxing; Qi, Desheng; Hu, Zhonghua; Zhang, Lina (Frontiers in Medicine, 2021)
Objective: Although hyperbilirubinemia has been associated with mortality in critically ill patients, yet no clinical studies dissect the effect of dynamic change of hyperbilirubinemia on long-term septic prognosis. The aim of the study is to investigate the specific stages of hyperbilirubinemia and potential risk factors on long-term outcomes in septic patients. Methods: In this retrospective observational cohort study, septic patients without previous chronic liver diseases were identified from the Medical Information Mart for Intensive Care III (MIMIC- III) database. We used propensity score (PS) to adjust the baseline differences in the septic patients with hyperbilirubinemia or not. The multivariate Cox was employed to investigate the predictors that influence clinical outcome in sepsis. Results: Of 2784 septic patients, hyperbilirubinemia occurred in 544 patients (19.5%). After propensity score matching, survival curve demonstrated that sepsis patients with the new onset of total bilirubin levels more than or equal to 5 mg/dL survived at significantly lower rates than those with total bilirubin levels less than 5 mg/dL. Multivariate Cox hazard analysis showed that patients with total bilirubin at more than or equal to 5 mg/dL during the course of sepsis exhibit 1.608 times (95% CI: 1.228-2.106) higher risk of one-year mortality than those with total bilirubin levels less than 5mg/dL. Also, age above 65 years old, preexisting malignancy, respiratory rate above 30 beats/min at admission, serum parameters levels within 24 hours admission containing INR above 1.5, platelet less than 50*10^9/L, lactate above 4 mmol/L, and bicarbonate less than 22 or above 29 mmol/L are the independent risk factors for long-term mortality of septic patients. Conclusions: After propensity score matching, serum total bilirubin levels at more than or equal to 5 mg/dL during hospitality is associated with increased long-term mortality for septic patients. This study maybe provide clinicians with some cutoff values for early intervention, which may improve the prognosis of patients with sepsis.